Customer-related social stressors and front line employee turnover intention: The mediating role of job-related anxiety - Abubakar, Muhtari Y. (2017)
Theory and empirical evidence suggests that customer stressors were positively related to frontline employee turnover intention. However, little work has focused on testing why and in what way customer stressors are related to such employee attitudinal outcome.To address this knowledge gap, we developed and tested a mediation model of turnover intention.Drawing on conservation of resources theory, we suggest that job-related anxiety might be a fundamental reason why customer-related stressors predicts front line employee turnover intention.The model was tested with a sample of 258 restaurant front line service employees. Results suggest a positive and significant relationship between customer-related stressors and employee turnover intention. Also, job-related anxiety was found to mediate the relationship between customer stressors and front line employee turnover intention. These results highlight the importance of job-related anxiety as a fundamental mechanism which explains why and in what way customer stressors are related to front line employee turnover intention.